Alteration of aluminium inhibition of synaptosomal (Na+/K+)ATPase by colestipol administration - Silva, V. S.
The ability of aluminium to inhibit the (Na+/K+)ATPase activity has been observed by several authors. During chronic dietary exposure to AlCl3, brain (Na+/K+)ATPase activity drops, even if no alterations of catalytic subunit protein expression and of energy charge potential are observed. The aluminium effect on (Na+/K+)ATPase activity seems to implicate the reduction of interacting protomers within the oligomeric ensemble of the membrane-bound (Na+/K+)ATPase. The activity of (Na+/K+)ATPase is altered by the microviscosity of lipid environment. We studied if aluminium inhibitory effect on (Na+/K+)ATPase is modified by alterations in synaptosomal membrane cholesterol content. Adult male Wistar rats were submitted to chronic dietary AlCl3exposure (0.03 g/day of AlCl3) and/or to colestipol, a hypolidaemic drug (0.31 g/day) during 4 months. The activity of (Na+/K+)ATPase was studied in brain cortex synaptosomes with different cholesterol contents. Additionally, we incubate synaptosomes with methyl-β-cyclodextrin for both enrichment and depletion of membrane cholesterol content, with or without 300 μM AlCl3. This enzyme activity was significantly reduced by micromolar AlCl3added in vitro and when aluminium was orally administered to rats. The oral administration of colestipol reduced the cholesterol content and concomitantly inhibited the (Na+/K+)ATPase. The aluminium inhibitory effect on synaptosomal (Na+/K+)ATPase was reduced by cholesterol depletion both in vitro and in vivo.